STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN PADA SERANGAN DIVE & WATERSPORT DI SERANGAN - I Wayan Tommy Wisnu Wardana; Ni Nyoman Menuh (STIMI Handayani Denpasar, 2018)
The purpose of this research is to know the marketing strategy to increase income on Dive & Watersport attack in attack. This qualitative descriptive analysis will use the analysis approach of SWOT. Strengths and weaknesses are analyzed by the service marketing mix like product, price, place, promotion, person, physical evidence and process. The opportunities and threats are analyzed with the responsive of security forces and the local communities and the beach cleanliness. The conclusion of this research is marketing strategy done by Dive & Watersport attack has not been able to increase sales because promotion activity which is not done effectively ie advertising activity (advertisement) is not done maximally. Promotional activities with the method of face-to-face (personal selling) has not done well, so there is often misunderstanding between employees and customers. Sales promotion activity has been done by Dive & Watersport Attack by giving special offer. Publicity activities have never been done by Dive & Watersport attacks. Suggestions given are the management of Dive & Watersport Attacks need to plan and allocate budget for promotional programs such as advertising on brochures and magazines. Create work training programs for employees about the deepening of the English language and the importance of personal selling as well as knowledge on how to communicate and good service to consumers.